Konya Şer’iyye sicillerinden130 nolu defterin değerlendirilmesi - Albayrak, Hafize (My University, 2010)
Çalıştığımız dönem H.1314–1318 yıllarına ait Konya Şer‘iyye Defteri’dir. Bu çalışma Konya’nın 130 No’lu Şer‘iyye Sicili Defteri’nin transkripsiyonu ve değerlendirilmesinden ibarettir. Tanzimat sonrasında, sicillerin konularının daraltılarak sadece belli konulara sıkıştırıldığını görsekte, sicillerin, mahalli tarihimiz için önemi büyüktür. Sicilimiz miras-tereke, evlenme- boşanma, nafaka, vakıf ve tevliyet konularını içermektedir. Çalışmamız; giriş ve 2 bölümden oluşmakta olup, girişte, şer‘iyye sicillerinin tanımı ve önemi ile şer‘iyye mahkemelerinin geçirdikleri süreç ele alınmıştır. Birinci bölümde, Konya halkının sosyal hayatı, ekonomik faaliyetleri, dini müesseseleri tespit edilerek Konya’nın mahalli tarihi hakkında bilgilere ulaşılmıştır. Konya’da kullanılan isimler, unvanlar, lakaplar, eşyalar ile şehirdeki mahalle, köy, kaza, nahiye isimleri tespit edilmiştir. Bununla birlikte dini, ticari ve sosyal müesseselerin de tespiti yapılmıştır. Ayrıca çalıştığımız dönemde Gayrimüslim halktan olan Ermeni ve Rumlar ile Müslüman halkın, bir arada hoşgörü içerisinde yaşadıkları görülmüştür. Defterimizde Gayrimüslimlerin miras- tereke ile ilgili şer‘î mahkemelere başvurmuş oldukları 3 tane dava vardır. Burada Gayrimüslimlerin kendi cemaat mahkemeleri yerine, Müslümanlara ait mahkemeleri tercih ettiklerini görmekteyiz. Defterimizde kadınların, haklarını aramak için rahatça dava açabildiklerini sosyal hayatın en küçük unsuru olan ailenin içerisindeki önemli yerlerini tespit etme imkânı bulduk. Aile kurumu incelenerek, ailedeki çocuk sayıları, eş sayısı, geçim kaynakları belirlenmiştir. Ailelerin ortalama 2–3 tane çocuk sayısına sahip olduklarını, ayrıca sanılanın aksine Osmanlı toplumunda çok eşliliğin tercih edilmediğini görmekteyiz. İkinci bölümde ise Konya şer‘iyye sicillerinden 130 nolu defterin transkripsiyonu yapılmıştır. Konya, Şer‘iyye Sicilleri, Sosyal ve Ekonomik Hayat.

The period and the point that we are examining and working on are the Islamic Court Records in the years of H.1314–1318 in the province of Konya. This study is comprised of the transcription of the Islamic Court Record Book of Konya numbered 130 and an evaluation of this record. Even though we see that in the aftermath of the Administrative Reforms (Tanzimat) the subjects of the records are narrowed and contracted to certain subjects, the importance of the records is great with respect to our local history. Our record covers such subjects as heritage, marriage, divorce, alimony, foundations, and bare trustee. Our study is made up of an introduction and two parts; and in the introduction a description of the Islamic Court Records and their importance is made and at the same time, the process through which the Islamic Courts had passed is taken up. In part I, the social life of the people of Konya, their economic activities, and religious organizations are examined, and information about the local history of Konya is reached. The names, titles, nick names, properties used in Konya and the names of the districts, villages, and towns in the province are all determined. And also, the religious, commercial, and social organizations are examined. In addition, during the period that we examined it is seen that the non-muslim society such as the Armenians and Greeks were living together in peace, indulgence and harmony. In the records we see 3 court cases in which the non-muslim people applied to the courts with respect to such subjects as heritage. Here we witness that non-muslim people g oto the Islamic Courts instead of going to their community courts. In our records we also witness that women were able to apply to thne courts for taking legal action. We also had the chance of determining the important parts of the life of the family, which is the smallest unit of the social life. The family life has been examined as a result of which the number of children, the number of wives in the family and the sources of living allowance of the family are determined. It has been found that families usually had 2-3 children, and that polygamy is not a preferred way of family life in the Ottoman Empire as opposed to the assumption with this respect. In part II, a transcription of Book number 130 of the Islamic Court Records of the province of Konya is made. Key Words: Konya, Islamic Court Records, Social and Economic Life.
Keywords: İslam Tarihi; Şer’iyye Sicilleri